Repertoires of Remembering: A Conceptual Approach for Studying Memory Practices in the Digital Ecosystem. (April 2020) - Burkey, Brant
Although the preponderance of collective memory research focuses on particular cultural repository sites, memorials, traumatic events, media channels, texts, or commemorative rituals as objects of study, this article fills a gap in literature by arguing that it is time to refresh established media-memory studies to now also consider how multimodal practices promise insight into the process of shared remembering in the new media ecology. The specific focus here is to propose a conceptual approach for how collective remembering can be observed, experienced, and researched in the digital ecosystem. In addition to a survey of collective memory and media memory studies, this article identifies specific ways to examine this issue by introducing the concepts of multimodal memory practices and platformed communities of memory, and by arguing that metadata analysis of digital practices should be considered a contemporary form of studying collective memory.